Nursery Resource Pack Mathematics Term 2 - The city school (Lahore, pakistan The city school)
The Nursery Resource Pack for Mathematics (Term 2) focuses on expanding foundational math skills. It introduces concepts like addition, subtraction, number sequencing, and simple measurements through engaging activities. The pack emphasizes hands-on learning with manipulatives to help children grasp abstract ideas. It also encourages problem-solving and logical reasoning. The goal is to build confidence in early numeracy while making learning enjoyable and interactive
The Nursery Resource Pack for Mathematics (Term 2) focuses on expanding foundational math skills. It introduces concepts like addition, subtraction, number sequencing, and simple measurements through engaging activities. The pack emphasizes hands-on learning with manipulatives to help children grasp abstract ideas. It also encourages problem-solving and logical reasoning. The goal is to build confidence in early numeracy while making learning enjoyable and interactive